Meals matter : a radical economics through gastronomy - Symons, Michael, 1945- (Arts and traditions of the table., 2020)
"In Gastronomics, Michael Symons provides an innovative history of the intersection of food history, philosophy and economics. Modern economic thought, Symons argues, is driven by a money-centric focus that benefits the interests of the 'corporate individual'-entities without finite appetites, motivated by an endless quest for financial growth-to the detriment of actual, corporeal individuals. Symons understands this shift as a modern devaluation of community and loss of a way of life that values food sharing, enjoyment and satiety. Covering a wide variety of thinkers-Jean Brillat-Savarin and Epicurus, Enlightenment philosophers Thomas Hobbes and John Locke, economic theorists Jean-Baptiste Say and Stanley Jevons, and neoliberals-Symons reads and critiques both popular and lesser-understood intellectuals to shed light into the 'economics of appetite' and the opposing 'economics of greed.' He calls for individuals to reject the self-interest of money pleasure and, through renewed attention to communal values of family, meal-sharing, food activism, and the defense of liberalism, advocates a return to a community-based philosophy of 'table pleasure.'"--